2012
DOI: 10.1519/jsc.0b013e31823a4063
|View full text |Cite
|
Sign up to set email alerts
|

Kettlebell Swing, Snatch, and Bottoms-Up Carry: Back and Hip Muscle Activation, Motion, and Low Back Loads

Abstract: The intent of this study was to quantify spine loading during different kettlebell swings and carries. No previously published studies of tissue loads during kettlebell exercises could be found. Given the popularity of kettlebells, this study was designed to provide an insight into the resulting joint loads. Seven male subjects participated in this investigation. In addition, a single case study of the kettlebell swing was performed on an accomplished kettlebell master. Electromyography, ground reaction forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 10 publications
2
67
0
Order By: Relevance
“…The external resistance used in the present study (16kg) is much less than that used in traditional lower-body free weight resistance exercise, but the kettlebell swing still includes substantial muscle mass activation (i.e., gluteal, hamstring, and back extensor muscles) (McGill & Marshall, 2012). This muscle activation appears to provide sufficient stimulus to induce a post-exercise increase in serum T concentrations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The external resistance used in the present study (16kg) is much less than that used in traditional lower-body free weight resistance exercise, but the kettlebell swing still includes substantial muscle mass activation (i.e., gluteal, hamstring, and back extensor muscles) (McGill & Marshall, 2012). This muscle activation appears to provide sufficient stimulus to induce a post-exercise increase in serum T concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…This exercise is performed with neutral spinal alignment and relies on the muscles of the posterior chain (i.e., gluteal, hamstring, and back extensor muscles) as the prime movers. Thus, the kettlebell swing involves a large muscle mass and results in substantial muscular activation in the posterior chain and abdominal muscles (McGill & Marshall, 2012). Because of this large muscle mass involvement, kettlebell swing exercise could induce an acute increase in hormones that are involved in modulating neuromuscular adaptations to training (e.g., improvements in performance).…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies examining kettlebell science have tended to focus on either physiological variables [5][6][7] or biomechanical variables [8,9]. A number of studies have also compared kettlebell exercise to treadmill running [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al concluded that kettlebell training may therefore be used to enhance aerobic capacity to the same extent as brisk walking. Mechanically focused studies of kettlebell exercise have reported that kettlebell exercise results in a hip-hinge squat pattern, eliciting rapid muscle activation-relaxation cycles, opposite in polarity to that of traditional Olympic weightlifting techniques [9]. Other work [8] has reported on the mechanical demands of the kettlebell swing specifically.…”
Section: Introductionmentioning
confidence: 99%
“…To determine which training regime elicits the greatest gain in strength and power, previous studies have focused on traditional lifts such as the bench press and back squat using electromyographic (EMG) and ground reaction force (GRF) analysis (Ebben & Jensen, 2002;Newton, Kraemer, Häkkinen, Humphries, & Murphy, 1996). Previous studies have also measured the impacts of using resistance bands and chains in conjunction with standard Olympic steel barbells (Ebben & Jensen, 2002), impacts of using kettlebell swings (McGill & Marshall, 2012) and plyometric exercises (Ellenbecker, Sueyoshi, & Bailie, 2014). Most of these studies are designed to measure relative muscle activation, which could evaluate the effectiveness of these non-traditional resistance training modalities.…”
Section: Introductionmentioning
confidence: 99%